Rock-magnetic and paleomagnetic data of composite sediment core ICDP5045-1 from Lake Ohrid, Balkans - Janna Just; Leonardo Sagnotti; Norbert R Nowaczyk; Alexander Francke; Bernd Wagner (PANGAEA, 2019)
This data table contains rock-magnetic parameters and paleomagnetic data of a 1.2 Ma sediment core composite ICDP 5045-1 from Lake Ohrid. Measurements have been conducted on discrete cube samples using a cryogenic magnetometer.
Supplement to: Just, Janna; Sagnotti, Leonardo; Nowaczyk, Norbert R; Francke, Alexander; Wagner, B (2019): Recordings of fast paleomagnetic reversals in a 1.2 ma greigite-rich sediment archive from lake ohrid, balkans. Journal of Geophysical Research: Solid Earth, 124(12), 12445-12464, https://doi.org/10.1029/2019JB018297